Multinational versus national firms on capital adjustment costs: A structural approach - Athanasios Lapatinas (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper provides an alternative perspective on the firm-level empirical analysis of the relation between foreign ownership and capital demand adjustment in host countries. The author estimates a dynamic structural model of investment on a sample of 4,672 Belgian firms for the period 2003 - 2010, permitting him to distinguish the "ownership status" of firms. He considers a dynamic discrete choice model of a general specification of adjustment costs including convex and non-convex components. The author uses the method of simulated moments in order to estimate the structural parameters. His results indicate that multinationals' affiliates face lower capital adjustment costs than national firms.
Keywords: F23; D24; D92; G31; 330; multinational firms; investment; capital adjustment costs; firm-level panel data